PENGARUH SISTEM FULL DAY SCHOOL TERHADAP KARAKTER SISWA DI SMA NEGERI 2 TELUK KUANTAN - Nikmatun Hasanah; Sopiatun Nahwiyah; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
character is a very important and basic thing. Remembering the importance of a character,education has the responsibility of instilling it through the learning process in school. Full Day SchoolProgram (Full Day School) is an effort carried out by educational institutions to instill character. all ofthat is done to protect students from moral decline.In general, this study aims to determine the effect of the Full Day School System on StudentCharacter at Teluk Kuantan 2 High School. The research method used is quantitative research, thepopulation of this study was 51 students, while the sample authors took as much as 50% of the totalsample of 28 students studied and 1 PAI teacher. Techniques for collecting data using, observation,interviews, questionnaires and documentation. Analysis Technique The data used is a simple linearregression technique.After the calculation is done, the writer draws conclusions, namely, "The statement tested isvalid in terms of salvation because r_hitung≥r_ (table) is the value of r_ (table) 0.2387. The measuringinstrument used in this study is reliable reliability. The results of a simple linear regression constantof 51,097 means that if the independent variable X (Full day School) has a value of 0, then thedependent variable Y (Student Character) is 51,097 (at full day school does not exist, studentachievement is still obtained at 51,097) .Regression coefficient value of full day school variable is 1,595, meaning that every increase infull day school is 1 (one) unit, it will increase learning achievement by 1,595. The results of thetemporary hypothesis state that ha is accepted because there is a significant effect between full dayschool on learning achievement.